Study of Leachate Contamination in Bantar Gebang Landfill to Its Shallow Groundwater using Natural Isotope Tracers of 18O, 2H and 3H - E.R. Pujiindiyati; P. Sidauruk (PPIKSN-BATAN, 2015)
Leaching from Bantar Gebang landfill, Jakarta’s main municipal landfill, especially from its two waste water treatment plants (plant A in zone-3 and plant B in Sumur Batu) to underlying aquifer has been studied using isotope techniques. The study was based on the abundances of the heavier isotopes in water molocules namely 18O, 2H (deuterium) and 3H (tritium). Because both water in the waste-water treatment plants and groundwater have undergone different independent physical processes, it was assumed that each water source has its own typical finger-print in term of the abundances of 18O, 2H (deuterium) and 3H (tritium). Leachate from the two waste water treatment plants have higher 2H, 3H activities, and physical parameters (EC, TDS, and pH) values than those of groundwater samples. Because of the age and size of the two waste water treatment plants are significantly different, it was also observed that the isotope contents of plant B, younger age and smaller size, was relatively lower in 2H values and 3H activities compared to those of plant A. These phenomena have been used to identify the leaching from waste-water treatment plants of Bantar Gebang landfill to the underlying aquifer. During the dry season, it was observed that 2H values in leachate were generally higher than those in rainy season. This result might be due to the extensive methane production in the treatment plants. Conversely, 18O-shifting in leachate from local meteoric line indicated that the leachate had experienced evaporation. Buried luminescent paints in the landfill were most likely the source of high tritium activity in leachate. Based on the samples collected from the study area (mostly from dug or bore wells), it was found that the underlying aquifer especially shallow groundwater has been contaminated up to as high as 33% with leachate.Received: 19 June 2014; Revised: 13 February 2015; Accepted 22 February 2015